2022
DOI: 10.3389/feart.2022.892316
|View full text |Cite
|
Sign up to set email alerts
|

The Last Glacial Maximum and Deglacial History of the Seno Skyring Ice Lobe (52°S), Southern Patagonia

Abstract: There are still many uncertainties about the climatic forcing that drove the glacier fluctuations of the Patagonian Ice Sheet (PIS, 38–55°S) during the last glacial period. A key source of uncertainty is the asynchrony of ice lobe fluctuations between the northern, central, and southern PIS. To fully understand the regional trends requires careful mapping and extensive geochronological studies. This paper presents geomorphological and geochronological reconstructions of the glacial and deglacial landforms form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 102 publications
1
0
0
Order By: Relevance
“…At Seno Skyring (Fig. 1B), Lira et al (2022) reported full glacial conditions during MIS 2, though implying that some of the samples could reflect previous exposure from earlier glaciations, in concordance with nearby records.…”
Section: Comparison With Other Glacial Records During Marine Isotopic...supporting
confidence: 68%
“…At Seno Skyring (Fig. 1B), Lira et al (2022) reported full glacial conditions during MIS 2, though implying that some of the samples could reflect previous exposure from earlier glaciations, in concordance with nearby records.…”
Section: Comparison With Other Glacial Records During Marine Isotopic...supporting
confidence: 68%